Friction and Wear Behaviors of Reduced Graphene Oxide- and Carbon Nanotube-Reinforced Hydroxyapatite Bioceramics - Hu, Huanlong; Li, Zhong; Sun, Wen; Li, Ruitao; Li, Hua; Khor, Khiam Aik (Frontiers in Materials, 2020)
Friction and wear properties play an important role in the long-term in vivo performance of load-bearing bioceramic implants. In this study, the friction and wear behaviors of hydroxyapatite (HA) reinforced with reduced graphene oxide (rGO) and rGO + carbon nanotube (CNT) hybrids were studied by ball-on-disk tests to understand the effects of nanocarbon content and morphology on the composites’ tribological behaviors. The intact and worn surfaces were characterized by optical microscopy, nanoindentation, field emission scanning electron microscopy, energy-dispersive X-ray spectroscopy, and Raman spectroscopy. We found that the incorporation of rGO and rGO + CNT hybrids in HA bioceramic both improved the friction and wear behaviors, and the highest wear resistance was achieved by employing 1 wt% rGO and 1 wt% CNT as reinforcements. The major reinforcing mechanism was the formation of carbonaceous films between the composite surfaces and counterbody, which served as solid lubrication films that resulted in a lower coefficient of friction, higher hardness, and increased hardness/modulus ratio. Importantly, CNT addition facilitated the uniform distribution of the reinforcements in the HA matrix and the pinning effects of CNT enhanced the connection between rGO and HA.